Alcohol intake during pregnancy among parturients in southern Brazil - Rodrigo Dalke Meucci; Janaina Salomão Saavedra; Elizabet Saes da Silva; Michele Avila Branco; Joelma Nunes de Freitas; Marina dos Santos; Juraci Almeida Cesar
Abstract Objectives: to assess alcohol intake prevalence and identify associated factors among pregnant women in the municipality of Rio Grande, RS, Brazil. Methods: this was a crosssectional study which included all parturient women residing in the municipality who gave birth in 2013. Two outcomes were characterized: alcohol intake during pregnancy and excessive alcohol intake during pregnancy. In the analysis, proportions were tested using the Chisquare test, whilst Poisson regression was used in the multivariate analysis. Results: 9.4% (CI95%= 8.210.5) of the 2,685 parturient women studied reported having consumed alcohol during pregnancy, with beer being most common beverage. Following adjustment, the factors associated with alcohol intake in pregnancy were: age ≥30 years, brown skin colour, living without a partner, low schooling, tobacco smoking and illicit drug use, having had more children and late onset of prenatal care. Excessive alcohol intake was found in 12.7% (CI95%= 8.616.9) of those who reported drinking during pregnancy and the factors associated with this practice were age ≥30 years, lower schooling and illicit drug use. Conclusions: this study found high alcohol intake during the gestation period and identified women more susceptible to this practice. There is an evident need for health professionals to work on preventing and handling alcohol intake among pregnant women in the municipality